2021
DOI: 10.3389/fimmu.2021.712122
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Antibodies for HIV-1 Prevention

Abstract: Given the absence of an effective vaccine for protection against HIV-1 infection, passive immunization strategies that utilize potent broadly neutralizing antibodies (bnAbs) to block acquisition of HIV-1 are being rigorously pursued in the clinical setting. bnAbs have demonstrated robust protection in preclinical animal models, and several leading bnAb candidates have shown favorable safety and pharmacokinetic profiles when tested individually or in combinations in early phase human clinical trials. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 131 publications
(176 reference statements)
0
58
0
Order By: Relevance
“…This suggests that there may be certain properties within the viral variants that infected the donors CAP206 and RV217.40512 (the donor from whom the VRC42 lineage was isolated) that gave rise to multiple MPER responses. Due to the highly conserved nature of the MPER, bNAbs targeting this region tend to be among the broadest antibodies isolated to date [39]. Sequential immunogens designed based on variants identified in CAP206 and/or RV217.40512 may enable the development of such responses in a vaccine setting.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be certain properties within the viral variants that infected the donors CAP206 and RV217.40512 (the donor from whom the VRC42 lineage was isolated) that gave rise to multiple MPER responses. Due to the highly conserved nature of the MPER, bNAbs targeting this region tend to be among the broadest antibodies isolated to date [39]. Sequential immunogens designed based on variants identified in CAP206 and/or RV217.40512 may enable the development of such responses in a vaccine setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although several standard virus panels such as the 12-strain ‘global’ panel ( 64 ) and the 118-strain multi-clade panel ( 87 ) have already been established, there is currently no consensus panel. As a consequence, the 291 antibodies were tested against different or only partially overlapping viral panels, making it difficult to compare them in terms of breadth and potency ( 88 ). Neutralization data against the global and the 118 multi-clade panel were downloaded separately from the CATNAP database.…”
Section: Methodsmentioning
confidence: 99%
“…Research has also shown that broadly neutralizing antibodies (bNAbs) can control HIV replication [ 212 217 ]. All bnAbs target the HIV-1 Envelope (Env) glycoprotein 120 (gp120) and gp41 [ 218 ]. The first-generation bNabs (b12, 447-52D, 2G12, 17b, 2F5, 4E10 and Z13) [ 219 221 ] generated little clinical effect on HIV [ 222 ].…”
Section: Hiv Cure Strategiesmentioning
confidence: 99%
“…The first-generation bNabs (b12, 447-52D, 2G12, 17b, 2F5, 4E10 and Z13) [ 219 221 ] generated little clinical effect on HIV [ 222 ]. Next, antibodies targeting the CD4 binding site (VRC01, 3BNC117, VRC01-LS, and VRC07-523LS), the glycan-rich V3 loop (10–1074 and PGT121), the V2-glycan site (PGDM1400, CAP256-VRC26.25) and MPER epitope (10E8) were identified [ 218 , 223 , 224 ]. All these bNAbs have shown different levels of protection against Simian Immunodeficiency Virus (SHIV) [ 225 228 ].…”
Section: Hiv Cure Strategiesmentioning
confidence: 99%
See 1 more Smart Citation